SketchUp 2014 for Architectural Visualization Second Edition. - Bleicher, Thomas (Packt Publishing, 2014)
In Detail SketchUp is an amazing and remarkably powerful 3D modeling software used by millions of architects, visualizers, and drafters across the globe. It allows you to create animated 3D drawings and photorealistic renderings that approximate real-life objects easily. This book is the perfect introduction to SketchUp 2014. It will help you to get started quickly and efficiently to produce and present commercial quality photorealistic or artistic outputs of your designs. It will teach you how to plan and set up the content of your scenes, use SketchUp and professional rendering software to produce stunning visuals and animations, and how to add an artistic touch to your images. Approach Beginning with a quick start tutorial which will get you up and running with SketchUp 2014 quickly, you will move on to learning the key skills you will need to wow your clients with stunning visualizations through a series practical steps, tips and tricks. Who this book is for If you are a SketchUp user, from an amateur right through to an architectural technician, professional architect, or designer, this is the book for you. This book is also suitable as a companion to any architectural design or multimedia course, and is accessible to anyone who has learned the basics of SketchUp.